2015
DOI: 10.1177/2158244015613108
|View full text |Cite
|
Sign up to set email alerts
|

Family Intervention in First-Episode Psychosis

Abstract: Family interventions have produced benefits on clinical and family outcomes in long standing psychosis. However, little is known about the efficacy of such interventions in the early stages of psychosis. This article reviews published research over the last two decades on family intervention in first-episode psychosis. Electronic databases, such as PubMed, PsycINFO, and ScienceDirect, have been systematically searched. In addition, an exhaustive Internet search was also carried out using Google and Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Results showed that there was a statistically significant difference between levels of income of the studied group regarding to the total expressed emotion. This result is consistent with sadath et al [4] who found that there was inverse correlation between monthly income and level of expressed emotion as many caregivers of psychosis were unable to afford their relatives' treatment expenses due to financial difficulties, which in turn increase level of expressed emotions. This relation explain the previous findings (level of expressed emotion did not improve to that significant level), because financial factors play a significant role in affecting on level of expressed emotion, and that factor cannot be controlled during the psycho educational intervention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Results showed that there was a statistically significant difference between levels of income of the studied group regarding to the total expressed emotion. This result is consistent with sadath et al [4] who found that there was inverse correlation between monthly income and level of expressed emotion as many caregivers of psychosis were unable to afford their relatives' treatment expenses due to financial difficulties, which in turn increase level of expressed emotions. This relation explain the previous findings (level of expressed emotion did not improve to that significant level), because financial factors play a significant role in affecting on level of expressed emotion, and that factor cannot be controlled during the psycho educational intervention.…”
Section: Discussionsupporting
confidence: 91%
“…This result is matched with the preexisting literature review, Mertinez et al [13] found that expressed emotion (criticism and EOI) were strongly high especially in the early stage of psychosis. In the same line Sadath et al [4] found that nearly half of the caregivers of his sample showed high level of expressed emotion.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In a previous systematic review, Bird et al (2010) examined a small number of randomized controlled trials ( n = 3) within specialist early intervention for psychosis services and found that service users whose families received FIp were less likely to relapse or be admitted to hospital at the end of treatment, compared to those receiving standard care. All other reviews examining the efficacy of FIp in early psychosis report mixed findings (Penn et al, 2005; Askey et al, 2007; Sadath et al, 2015). However, there have been a number of limitations to previous reviews, including not using a systematic search strategy (Askey et al, 2007), only examining RCTs taking place within specialist early intervention for psychosis services (Bird et al, 2010), including mixed-length illness samples (Pharoah et al, 2010) and multi-element interventions (Penn et al, 2005) or limiting the review period to the last two decades (Sadath et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…All other reviews examining the efficacy of FIp in early psychosis report mixed findings (Penn et al, 2005; Askey et al, 2007; Sadath et al, 2015). However, there have been a number of limitations to previous reviews, including not using a systematic search strategy (Askey et al, 2007), only examining RCTs taking place within specialist early intervention for psychosis services (Bird et al, 2010), including mixed-length illness samples (Pharoah et al, 2010) and multi-element interventions (Penn et al, 2005) or limiting the review period to the last two decades (Sadath et al, 2015). Further, with exception of Bird et al (2010), no previous reviews have employed a meta-analytic approach to provide quantitative synthesis of the evidence.…”
Section: Introductionmentioning
confidence: 98%